TINDAKAN CONTEMPT OF COURT DALAM PROSES PENYELESAIAN SENGKETA PERDATA DI INDONESIA DAN PERBANDINGANNYA DENGAN SINGAPURA - Muhammad Ridwan Fadhly; Anita Afriana; Sherly Ayuna Putri (ADHAPER: Jurnal Hukum Acara Perdata, 2020)
Contempt of Court behavior is rife in the process of resolving court disputes in Indonesia including civil disputes. Contempt of Court actions constitute an insult to the judiciary so that it is appropriate to be sanctioned as a deterrent eff ect. This study aims to determine the actions that can be qualified as a Contempt of Court in the settlement of civil disputes, as well as understanding the law enforcement of the Contempt of Court in the practice of dispute resolution in court and its comparison with Singapore. This study uses normative juridical methods. This method is carried out by examining library materials in the form of legislation, doctrine, and other scientific papers related to the Contempt of Court and interviews with sources to obtain primary data as a secondary data extras, which is then analyzed in a qualitative juridical analysis. The results of the research show that Civil Contempt actions in the practice of civil dispute resolution processes can be interpreted as any act done intentionally not in compliance with every summons, orders, decrees, warnings, or decisions issued by the court resulting in losses to parties who litigate and undermine the authority, dignity and honor of the court. Law enforcement against the actions of Civil Contempt of Court in Indonesia is still considered less eff ective when compared to Singapore. Singapore has included its arrangements in written rules governing the qualifi cations of actions and sanctions imposed. In addition to administrative and civil sanctions, criminal sanctions also apply in order to increase the effectiveness of enforcement of the Civil Contempt of Court.